Study and Analysis of the Effective Geometries for the Piezoresistive Pressure Sensors (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
THE REPORTED WORK IS ON THE DESIGN AND SIMULATION OF MICROELECTROMECHANICAL SYSTEMS (MEMS) BASED SILICON PIEZORESISTIVE PRESSURE SENSOR DEPLOYED TOSENSE PRESSURE IN THE RANGE OF 0 TO 1.1 BAR. THE PRESSURE IS APPLIED ON THE DIAPHRAGM CONSISTING OF FOUR PIEZORESISTORS CONNECTED IN THE WHEATSTONE BRIDGE CONFIGURATION. THE INDUCED STRESS AS A RESULT OF THE PRESSURE CAUSES CHANGE IN RESISTANCE OF PIEZORESISTORS DUE TO PIEZORESISTIVE EFFECT. THE DESIGN AND SIMULATION OF THE SENSORS PRIOR TO FABRICATION HELPS US TO OPTIMIZE THE DIAPHRAGM THICKNESS AND SIZE. MEANDER SHAPED PIEZORESISTORS WITH DIFFERENT NUMBER OF TURNS ARE STUDIED IN ORDER TO FIND OUT THE BEST CONFIGURATION FOR HIGH SENSITIVITY AND LINEARITY. THE DESIGN AND SIMULATION IS CARRIED OUT USING FEM (FINITE ELEMENT METHOD) BASED COMSOLMULTIPHYSICS. BASED ON THE SIMULATION RESULTS, THE TWO-TURN CONFIGURATION IS FOUND TO HAVE THE BEST SENSITIVITY OF 4.181 MV/V/BAR AND THE ONE TURN CONFIGURATION GIVES THE LEAST NON-LINEARITY OF 0.5051 %